La motivation des étudiants à l’entrée à l’université : quels effets directs ou indirects sur la réussite ? - Sophie Morlaix; Marielle Lambert-Le Mener (Recherches en Éducation)
The aim of this article is the extent of the role of motivational abilities of students on academic success by adopting a quantitative and integrative approach. To this end, the data collected on students in the first year of Bachelor of three streams are used to control a variety of factors related to socio-demographic and educational characteristics of students. Measured in the framework of the theory of self-analyzes suggest that intrinsic motivation positively influences while amotivation results in lower performance. Moreover, motivation is an asset for good students, but plays a more modest role in how students and even zero for the weak. Finally, the motivation appears to be a mediating variable that expresses the indirect effects of social origin and educational background of success.